The Shark Basal Hypothalamus: Molecular Prosomeric Subdivisions and Evolutionary Trends - Santos-Durán, Gabriel N.; Ferreiro-Galve, Susana; Menuet, Arnaud; Mazan, Sylvie; Rodríguez-Moldes, Isabel; Candal, Eva (Frontiers in Neuroanatomy, 2018)
The hypothalamus is a key integrative center of the vertebrate brain. To better understand its ancestral morphological organization and evolution, we previously analyzed the segmental organization of alar subdivisions in the catshark Scyliorhinus canicula, a cartilaginous fish and thus a basal representative of gnathostomes (jawed vertebrates). With the same aim, we deepen here in the segmental organization of the catshark basal hypothalamus by revisiting previous data on ScOtp, ScDlx2/5, ScNkx2.1, ScShh expression and Shh immunoreactivity jointly with new data on ScLhx5, ScEmx2, ScLmx1b, ScPitx2, ScPitx3a, ScFoxa1, ScFoxa2 and ScNeurog2 expression and PCNA immunoreactivity. Our study reveals a complex genoarchitecture for chondrichthyan basal hypothalamus on which a total of twenty one microdomains were identified. Six belong to the basal acroterminal region, the rostral-most point of the basal neural tube; seven are described in the tuberal region (Tu/RTu); four in the perimamillar region (PM/PRM) and four in the mamillar one (MM/RM). Interestingly, the same set of genes does not necessarily describe the same microdomains in mice, which in part contributes to explain how forebrain diversity is achieved. This study stresses the importance of analyzing data from basal vertebrates to better understand forebrain diversity and hypothalamic evolution.